1993
DOI: 10.1111/j.1442-9993.1993.tb00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Water relations of the canopy species in a Banksia woodland, Swan Coastal Plain, Western Australia

Abstract: Diurnal and seasonal water relations were measured in selected species of a Banksia woodland at a site with groundwater at a depth of 6–7 m. The canopy co‐dominants Banksia attenuata and Banksia menziesii exhibited similar patterns of variation in water relations, both diurnally and seasonally. Stomatal conductance was usually 0.4–0.5 cm s−1 diurnally and seasonally and, generally, did not respond to water deficit and other factors. Transpiration was correlated positively with factors indicative of atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
(30 reference statements)
5
18
0
Order By: Relevance
“…However, B. prionotes utilised a larger proportion of groundwater at all times (range in groundwater use of 20-100%) perhaps due to its fastgrowing habit, root distribution, or the results are an artefact of differences in the mixing model used to infer dependence. Groundwater use by the lower and upper slope trees is consistent with observations reported for B. attenuata and B. menziesii trees overlying a similar depth to groundwater of 6-7 m (Dodd and Bell 1993). Based on shoot water potential analysis alone, it was concluded that these species were able to access and utilise groundwater in late summer.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, B. prionotes utilised a larger proportion of groundwater at all times (range in groundwater use of 20-100%) perhaps due to its fastgrowing habit, root distribution, or the results are an artefact of differences in the mixing model used to infer dependence. Groundwater use by the lower and upper slope trees is consistent with observations reported for B. attenuata and B. menziesii trees overlying a similar depth to groundwater of 6-7 m (Dodd and Bell 1993). Based on shoot water potential analysis alone, it was concluded that these species were able to access and utilise groundwater in late summer.…”
Section: Discussionsupporting
confidence: 82%
“…To address this issue, the present study investigated the water sources used by B. ilicifolia, which is limited in its distribution to lowlying areas of the landscape and therefore shallow depths to groundwater, and more drought-tolerant species, such as B. attenuata (Dodd and Bell 1993), which occurs across a broad range of topography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large differences in rainfall between the two years examined (522 mm cf 1062 mm) led to a greater proportion of rainfall being transpired in 2003 than 2004 (61% vs. 42% estimated using the E sv method and 71% vs. 37% estimated using the E PM method). These estimates of the proportion of rainfall lost as transpiration are in agreement with those for a Banksia woodland in Western Australia (Dodd and Bell, 1993) and an open wet schlerophyll forest in the Australian Capital Territory (Leuning et al, 2005). Despite the reduction in the proportion of rainfall used in transpiration when more rain occurred, the volume transpired increased with increasing rainfall (317 mm vs. 443 mm estimated using the E sv method and 371 mm vs. 398 mm estimated using the E PM method).…”
Section: Annual Stand Water Use and Water Budgetsupporting
confidence: 61%
“…Redistribution of ground water over summer is an important function of deep-rooted species due to the extremely low water holding capacity of Banksia woodland soils (Dodd & Bell 1993, Pate & Bell 1999. Hydraulic lift facilitates survival of shallower rooted understorey species (roots < 2 m) by providing sustained moisture over the dry summer months (Caldwell et al 1998, Groom 2004).…”
Section: Shifts In Trait Valuesmentioning
confidence: 99%